Multistage Multiobjective Volt/VAR Control for Smart Grid-Enabled CVR with Solar PV Penetration - Singh S.; Babu Pamshetti V.; Thakur A.K.; Singh S.P. (My University, 2025)
This article investigates the need of coordinated operation of multiple voltage regulation devices under different time scales to enhance energy efficiency via conservation voltage reduction (CVR) in distribution networks in the presence of high photovoltaic (PV) penetration. A multistage multiobjective Volt/VAR control strategy for smart grid-enabled CVR has been proposed. In order to maximize the benefits of CVR, the method has been implemented in multiple stages of slow and fast time scale control periods for planning and real-time operations, respectively. The stochastic multiobjective Volt/VAR optimization considering uncertainty and forecasting errors has been formulated for the planning stage. However, in real-time operation, an adaptive Volt/VAR droop-controlled approach has been proposed for fast time controllers to mitigate voltage fluctuations during the sudden change in PV active power output. Besides, the economic impact of CVR in terms of cost savings has been investigated. The proposed control algorithms have been validated in real-time co-simulation platform. The simulated results demonstrate a higher reduction in peak demand, daily energy demand, and system losses. Further, a higher reduction in power purchase cost has been achieved in the presence of PV system with CVR in comparison to PV alone. Moreover, the proposed control algorithms work well in real-time operation under intermittency in PV power output also. © 2007-2012 IEEE.